Managing family life and tertiary studies: exploring the educational experiences of Muslim, non-traditional women students - Saloojee, Melanie Fiona (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEdPsych)--Stellenbosch University, 2022.